2018
DOI: 10.1093/pcp/pcy060
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR169o, an Overlapping MicroRNA in Response to Both Nitrogen Limitation and Bacterial Infection, Promotes Nitrogen Use Efficiency and Susceptibility to Bacterial Blight in Rice

Abstract: Limiting nitrogen (N) supply contributes to improved resistance to bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo) in susceptible rice (Oryza sativa). To understand the regulatory roles of microRNAs (miRNAs) in this phenomenon, 63 differentially expressed overlapping miRNAs in response to Xoo infection and N limitation stress in rice were identified through deep RNA sequencing and stem-loop quantitative real-time PCR. Among these, miR169o was further assessed as a typical overlapping miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…Recent reports on miRNAs in rice-Xoo interaction were mostly sequencing-based, and the samples were collected from single less-resistant genotype or/and its transgenic resistant derivatives [28,29,32]. To exclude the limitation of single material and the unpredictable impact of transgenic approach and resistant gene, the rice accessions IR24 and IRBB5 were chosen to construct small RNA libraries for investigate the regulatory roles of miRNAs because of no miRNA targeting the Xoo-resistant gene xa5 in bioinformatic analysis (http://plantgrn.noble.org/v1_psRNATarget/).…”
Section: Ir24 and Irbb5 Were Unbiased To Unmask The Mirnas Function Imentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports on miRNAs in rice-Xoo interaction were mostly sequencing-based, and the samples were collected from single less-resistant genotype or/and its transgenic resistant derivatives [28,29,32]. To exclude the limitation of single material and the unpredictable impact of transgenic approach and resistant gene, the rice accessions IR24 and IRBB5 were chosen to construct small RNA libraries for investigate the regulatory roles of miRNAs because of no miRNA targeting the Xoo-resistant gene xa5 in bioinformatic analysis (http://plantgrn.noble.org/v1_psRNATarget/).…”
Section: Ir24 and Irbb5 Were Unbiased To Unmask The Mirnas Function Imentioning
confidence: 99%
“…Moreover, osa-mi319/OsTCP21 [27], osa-miR444/OsMADS57 [26], osa-miR171b/OsSCL6-IIa, OsSCL6-IIb, OsSCL6-IIc [25] and osa-miR528/OsAO [24] regulatory units could change the disease development caused by rice stripe virus and rice ragged stunt virus, respectively. However, only two regulatory units, osa-miR156/OsIPA1 [31] and osa-miR169o/OsNF-YA [32], were published, which mediated immunity to Xoo. Integrating analysis of small RNA sequencing and degradome data showed that 29 DE known miRNAs might be involved in anti-bacterial regulatory mechanism in BB.…”
Section: Multiple Mirna/targets Regulatory Units Drives Flexible Defementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that miRNAs are associated with rice immune responses against pathogens such as Magnaporthe oryzae ( M. oryzae ) (Li et al , , ; Wang et al , ; Zhang et al , ), Rice ragged stunt virus (RRSV) (Zhang et al , ), rice stripe virus (RSV) (Wu et al , ), and Xanthomonas oryzae pv. oryzae ( Xoo ) (Zhao et al , ; Yu et al , ). For example, overexpression of miR160a and miR398b in transgenic rice plants enhanced rice blast resistance by increasing hydrogen peroxide accumulation at the infection site and upregulating the expression of defence‐related genes (Li et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of miR160a and miR398b in transgenic rice plants enhanced rice blast resistance by increasing hydrogen peroxide accumulation at the infection site and upregulating the expression of defence‐related genes (Li et al , ). Moreover, the miR169 family negatively regulates rice immunity against M. oryzae and Xoo by differentially repressing the expression of its target genes, the nuclear factor Y ‐ A ( NF‐YA ) family members (Li et al , ; Yu et al , ). In addition, miR319‐ mediated regulation of OsTCP21 might affect rice resistance against blast disease and RRSV infection by manipulating jasmonic acid (JA) signalling (Zhang et al , , ).…”
Section: Introductionmentioning
confidence: 99%